2022
DOI: 10.3390/ijms232416032
|View full text |Cite
|
Sign up to set email alerts
|

Primary Breast Angiosarcoma: Comparative Transcriptome Analysis

Abstract: Primary breast angiosarcoma, with de novo appearance and not associated with exposure to radiation or lymphedema, is a rare pathology representing less than 0.05% of the neoplasms related to this organ. The pathology is characterized by its aggressiveness, poor prognosis, and difficulties in its differential diagnosis. This article reports the case of a 55-year-old white woman with no family history of cancer, with a rapidly growing mass in the left mammary gland that ulcerates and bleeds. It is confirmed as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Garbo et al reviewed the benefits and the limits of RNA therapeutics by describing the non-coding RNA molecules that are being tested in clinical trials, and by analyzing the delivery strategies for different therapeutical applications [ 5 ]. Rincon-Riveros et al reported an interesting case study in which the authors utilized comparative transcriptome analysis for the diagnosis of primary breast angiosarcoma, a rare cancer representing less than 0.05% of breast cancer cases [ 6 ]. This study highlighted the use of RNA expression to predict an immune and inflammatory response in patients.…”
mentioning
confidence: 99%
“…Garbo et al reviewed the benefits and the limits of RNA therapeutics by describing the non-coding RNA molecules that are being tested in clinical trials, and by analyzing the delivery strategies for different therapeutical applications [ 5 ]. Rincon-Riveros et al reported an interesting case study in which the authors utilized comparative transcriptome analysis for the diagnosis of primary breast angiosarcoma, a rare cancer representing less than 0.05% of breast cancer cases [ 6 ]. This study highlighted the use of RNA expression to predict an immune and inflammatory response in patients.…”
mentioning
confidence: 99%